IMPLEMENTASI APLIKASI BANTULPEDIA DALAM MEWUJUDKAN PROGRAM SMART GOVERNANCE DI KABUPATEN BANTUL - Arsyad Agung Kurniawan; Bernadeta Nefo Eka Wijayanti (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This study aims to analyze the implementation of the Bantulpedia application in supporting the smart governance program in Bantul Regency and to identify its inhibiting factors. The research employs a descriptive qualitative method using George C. Edward III’s policy implementation model, which consists of four main indicators: communication, resources, disposition, and bureaucratic structure. The findings show that Bantulpedia has contributed to improving transparency, efficiency, and accountability in digital public services in Bantul Regency, although its implementation remains suboptimal. The main obstacles include the lack of comprehensive and continuous public outreach, limited technical capacity of human resources, the absence of standardized operating procedures (SOPs) for inter-agency integration, and weak coordination and data interoperability across sectors. This study recommends strengthening segmented public communication strategies, enhancing human resource capacity through regular training, developing integrated inter-agency SOPs, and conducting periodic evaluations of the application’s performance to support the realization of intelligent, participatory, and responsive governance in Bantul Regency.